2016
DOI: 10.1007/s10661-016-5551-5
|View full text |Cite
|
Sign up to set email alerts
|

Plants’ healthiness assessment as part of the environmental monitoring of protected mountainous area in the example of Karkonosze (Giant) Mts. (SW Poland)

Abstract: The aim of phytopathological monitoring is to check the healthiness of plants and observe the changes that occur in their populations. In the vast majority, these types of observations are conducted in agriculture and forestry. An interesting aspect of phytopathological monitoring is the assessment of the origin of the plant species. The research of fungal communities (including pathogens) in plants may, for example, indicate the relic nature of the plant species. Reduction of the occurrence or disappearance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
7
0
3
Order By: Relevance
“…Najliczniej izolowanym z porażonych liści R. japonica był saprotrof, uważany także za wtórnego patogena -grzyb A. alternata (stanowił blisko 80% wszystkich wyizolowanych kolonii uzyskanych z Wigierskiego Parku Narodowego). Jest to takson często izolowany zarówno z żywych, jak i uszkodzonych tkanek, doprowadzający czasami do patogenezy i wystąpienia objawów chorobo wych u roślin (Pusz 2016). Interesujący jest fakt, że A. alternata dominował w mykobiocie porażonych liści rdestowca rosnącego na terenie Wigierskiego Parku Narodowego, natomiast na osobnikach pochodzących z Tatrzańskiego Parku Narodowego, stanowił nieco ponad 14%.…”
Section: Wyniki I Dyskusja / Results and Discussionunclassified
“…Najliczniej izolowanym z porażonych liści R. japonica był saprotrof, uważany także za wtórnego patogena -grzyb A. alternata (stanowił blisko 80% wszystkich wyizolowanych kolonii uzyskanych z Wigierskiego Parku Narodowego). Jest to takson często izolowany zarówno z żywych, jak i uszkodzonych tkanek, doprowadzający czasami do patogenezy i wystąpienia objawów chorobo wych u roślin (Pusz 2016). Interesujący jest fakt, że A. alternata dominował w mykobiocie porażonych liści rdestowca rosnącego na terenie Wigierskiego Parku Narodowego, natomiast na osobnikach pochodzących z Tatrzańskiego Parku Narodowego, stanowił nieco ponad 14%.…”
Section: Wyniki I Dyskusja / Results and Discussionunclassified
“…Grzyb ten jest polifagiem, rozwijającym się w szerokim spektrum temperatury (Govrin i Levine 2000). Może powodować choroby zarówno roślin uprawnych, jak i dziko rosnących (Pusz 2016). O jego agresywności świadczy także fakt infekowania organów roślinnych w hodowli in vitro, a także gametofitów paproci (San Francisco i Cooper-Driver 1984).…”
Section: Wyniki I Dyskusja / Results and Discussionunclassified
“…Only in fungi do the aforementioned factors determine the appearance of the colony and, in many cases, facilitate the production of distinctive morphological forms (such as fungal spores) that can prove useful in the identification process [36]. This is why the majority of the fungi analyzed using the classical method can be identified down to a specific complex, genus or section [37,38]. This is one of the reasons why most of the fungi sampled in this study were identified as belonging to a complex (e.g., the C. cladosporioides sp.…”
Section: Discussionmentioning
confidence: 99%
“…According to the existing Fungi Wood on decomposition scale Sampling location 1 2 3 4 5 I II III I II III I II III I II III I II III I II Wood on decomposition scale Sampling location 1 2 3 4 5 I II III I II III I II III I II III I II III I II [46]. These fungi may also constitute an element of the mycoflora that acts as an inhibitor of natural cycles of renewal, since they pose a threat to seedlings and young trees [9], as well as herbaceous plants [38]. Nevertheless, in environments that experience low human disturbance, Fusarium fungi are a regular component of plant communities and, unlike in agricultural crops or nurseries, their incidence is not of epidemic proportion [47].…”
Section: Discussionmentioning
confidence: 99%